COMBINATIVE EFFECTS OF THANH HAO MIET GIAP THANG (SWEET WORMWOOD AND TORTOISE SHELL DECOCTION) INGREDIENTS ON ANTIOXIDATIVE ACTIVITY IN VITRO - Nuong, Nguyen My; Vy, Nguyen Thuy; Duong, Ho-Huynh Thuy (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Traditional formulae usually exhibit therapeutic effects through the combinations of different ingredients. The purpose of this study was to investigate in vitro anti-oxidative activity of Thanh Hao Miet Giap Thang (THMGT) (Sweet Wormwood and Tortoise Shell Decoction) formula and the interactions of its ingredients leading to the overall anti-oxidative effect. Materials and Methods: We prepared 31 combinations containing two to four of the five ingredients including Herba Artemisia apiacea L (HbA), Carapax Trionycis (Tryonix sinensis) (CT), Rhizoma Anemarrhenae (Anemarrhena asphodeloides) (RzA), Radix Rehmanniae (Rehmannia glutinosa Libosch) (RdR), Moutan Cortex (Paeonia suffruticosa) (MC). These combinations were tested for anti-oxidative activity using DCFH-DA and DPPH assays on Hep G2 cells. We also analyzed changes in expression of genes involved in antioxidant defense system including Nuclear Factor Erythroid-Derived 2-Like 2 (NFE2L2), catalase (CAT), heme oxygenase-1 (HO-1), glutathione peroxidase (GPx), cytoplasmic superoxide dismutase (SOD1), mitochondrial superoxide dismutase (SOD2). Results: The complete formula and all combinations containing Moutan Cortex showed high antioxidant activity in both radical solution-based chemical assay and cellular-based assay. On the contrary, Carapax Trionycis displayed inhibitory effect on the overall antioxidant activity when present in a combination, an effect clearly emphasized in cellular-based assay. Hep G2 cells treated with the formula showed increased gene expression of HO-1 and SOD2 while expression of CAT, SOD1, GPx was unchanged. Conclusion: Our results suggested that THMGT had anti-oxidative activity essentially through intrinsic reducing capacities and the overall activity of the formula resulted from enhancing and inhibiting interactions of ingredients.